2009
DOI: 10.1007/s11606-009-1207-2
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Granulomatous Mastitis: Case Reports and Review of Literature

Abstract: Idiopathic granulomatous mastitis (IGM) is an uncommon benign disorder of the breast that can mimic two frequent breast disorders, breast carcinoma and breast abscess. In this report, we present two patients seen in a community teaching hospital over a period of one year, diagnosed with IGM after histological evaluation. One patient responded well to immunosuppressive therapy, but the second patient required bilateral mastectomy due to the severe and recurrent nature of the disease. IGM is a disorder that shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
136
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(157 citation statements)
references
References 26 publications
1
136
1
8
Order By: Relevance
“…A study of 1106 cases of benign conditions of the breast revealed the figure of 1.8% for GM [1], while in a study in Turkey, it constituted 6.8% of their surgical benign specimens [3]. The disease usually occurs in childbearing ages in the 3 rd and 4 th decades of life, but a range of 11 to 83 years has been reported in the literature [1,3,4]. Almost all affected women reported in different series have had a history of pregnancy and lactation, recent in many cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study of 1106 cases of benign conditions of the breast revealed the figure of 1.8% for GM [1], while in a study in Turkey, it constituted 6.8% of their surgical benign specimens [3]. The disease usually occurs in childbearing ages in the 3 rd and 4 th decades of life, but a range of 11 to 83 years has been reported in the literature [1,3,4]. Almost all affected women reported in different series have had a history of pregnancy and lactation, recent in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all affected women reported in different series have had a history of pregnancy and lactation, recent in many cases. The etiology is unknown; association of the disease with pregnancy, breastfeeding and oral contraceptives (OCP) has been mentioned [1,[3][4][5][6]. Imoto et al focus on an association of the disease with hormonal changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations